AqdiLab: interactive simulation of Muamalat contracts - Meerangani, Khairul Azhar; Abdul Hamid, Mohammad Fahmi; Ahad, Norhana; Rosele, Muhammad Ikhlas (2025)
AqdiLab: Interactive Simulation of Muamalat Contracts is a teaching and learning innovation developed for the course IMU102 – Introduction to Fiqh Muamalat at UiTM. This approach integrates interactive simulations with real-world case studies to help students understand the structure and application of Islamic contracts such as sales, leasing, and partnerships. Students are presented with practical scenarios and are required to solve them using principles derived from classical fiqh texts and contemporary references. The method aims to enhance students’ comprehension of key concepts and contractual logic through an engaging and contextual learning experience. AqdiLab incorporates elements such as quizzes, clues, case-based experiments, and rewards to encourage active student participation. It addresses the limitations of conventional teaching methods by offering a more dynamic, flexible, and student-centered learning environment. Its effectiveness was evaluated through student feedback and lecturer reflections. Findings show that 70% of students reported an improved understanding, 85% found the approach more engaging than traditional methods, and 80% of lecturers agreed that this innovation enhanced their teaching delivery. Overall, AqdiLab not only enriches the simulation-based pedagogical approach but also demonstrates its potential as a reference model for interactive and applied learning in the field of Islamic commercial jurisprudence, aligned with 21stcentury education goals.